2015
DOI: 10.15376/biores.10.1.1198-1212
|View full text |Cite
|
Sign up to set email alerts
|

Wood Veneer Dyeing Enhancement by Ultrasonic-assisted Treatment

Abstract: To extend the potential application of ultrasonic treatment in dyeing lowquality wood to improve decorative value, wood veneers were dyed with an ultrasonic assisted dyeing system. The effects of ultrasonic power, dye concentration, dyeing time, and temperature of ultrasonic-assisted treatment on dye-uptake, chromatic value, crystallinity, thermal stability, chemical structure, and microstructure for dyed wood veneer were investigated. The dye-uptake, chromatic value, and dyeing rate were improved by ultrasoni… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
29
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 26 publications
(29 citation statements)
references
References 11 publications
0
29
0
Order By: Relevance
“…The cellulose, hemicellulose, and lignin exhibited an absorption peak at 2925 cm -1 , which was attributed to the resonance of C-H. The absorption peak at 1740 cm -1 was quite obvious (Table 3), associated with the stretching vibration of C-O, which indicated that there was a mass of carbohydrate, aldehyde, and keto in basswood (Ding 2011;Li 2011;Liu et al 2015).…”
Section: Ftir Analysismentioning
confidence: 99%
See 1 more Smart Citation
“…The cellulose, hemicellulose, and lignin exhibited an absorption peak at 2925 cm -1 , which was attributed to the resonance of C-H. The absorption peak at 1740 cm -1 was quite obvious (Table 3), associated with the stretching vibration of C-O, which indicated that there was a mass of carbohydrate, aldehyde, and keto in basswood (Ding 2011;Li 2011;Liu et al 2015).…”
Section: Ftir Analysismentioning
confidence: 99%
“…There are various kinds of dyes applied in wood staining, such as acid dyes (Zhao et al 1993;Duan et al 1997;Chen et al 2000;Yu et al 2001;Guo 2006;Chang et al 2008;Shao et al 2011;Liu et al 2015), disperse dyes (Qu 2007), and basic dyes (Guan 2003;Li 2007;Chen 2008;Chang 2010), but there exist some problems in the above methods. In the process of acid dye and basic dye treatment, the pH of the dye bath should be controlled with the assistance of some reagents that are not environmentally friendly.…”
Section: Introductionmentioning
confidence: 99%
“…However, the tone is relatively bland, and the superficial color is variational, which leads to the reduced aesthetic value for fast-growing wood. Wood dyeing, an advanced and mature technique, can eliminate color differences, simulate the color properties of highly valuable wood species, and improve the visual characteristics of wood products [3,4]. The dyed wood products have been widely applied in furniture, flooring, interior decoration, and sports equipment, etc., and generated tremendous social and economic benefits [5][6][7].…”
Section: Introductionmentioning
confidence: 99%
“…Sun and Yu [6] investigated the ultrasonic effects on dye uptake using poplar wood veneers and acidic dyes as raw materials, and found that ultrasound increased dye uptake under optimal conditions. Liu et al [3] studied the properties of dyed poplar wood with acid red GR dye using ultrasonicassisted treatment and concluded that dye uptake, chromatic value and wood permeability were improved. Nevertheless, the acid dyes used in their researches permeated the wood without any chemical reaction, which resulted in dye running off easily from the wood.…”
Section: Introductionmentioning
confidence: 99%
“…To improve the durability and fire safety of this biodegradable material, various chemical or physical methods have been utilized to manufacture preservative-treated and fire-retardant wood products (Marney and Russell 2008;Lowden and Hull 2013). Furthermore, many new functional materials such as dyed wood, electromagnetic shielding plywood, sound absorption wood-based material, wooden electric heating composite, and wood-based flexible supercapacitors have been developed to expand the application range of wood materials and to improve the added value of wood products (Lu et al 2014;Yuan and Fu 2014;Liu et al 2015;Lv et al 2015;Smardzewski et al 2015). With continuous increase of consumer demands for high-quality living environments, it is necessary to develop smart wood materials that spontaneously change their properties with the variation of environmental factors (Li et al 2010).…”
Section: Introductionmentioning
confidence: 99%